2022
DOI: 10.3389/fpsyt.2022.1078161
|View full text |Cite
|
Sign up to set email alerts
|

The changing relationship between health risk behaviors and depression among birth cohorts of Canadians 65+, 1994–2014

Abstract: Background and objectiveThe older adult residents of Canada form an increasingly larger proportion of the population and are becoming better educated and have more income. Depression is a common mental disorder, particularly among seniors. Several health risk behaviors–physical inactivity, tobacco use, and alcohol consumption–are linked to mental health problems. This study examines whether these health risk behaviors and their association with depression among Canadians 65+ born in eight cohorts between 1910–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This survey explored depression in participants aged ≥45 years. Furthermore, based on pooled data among Canadians aged ≥65 years, cigarette smoking was constantly and progressively associated with depression 14 . Ever smokers comprised participants who were either former (ex) smokers and/or current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…This survey explored depression in participants aged ≥45 years. Furthermore, based on pooled data among Canadians aged ≥65 years, cigarette smoking was constantly and progressively associated with depression 14 . Ever smokers comprised participants who were either former (ex) smokers and/or current smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Talati et al (155) found that while overall tobacco use declined in the U.S. from the 1940s to 1980s, the proportion of smokers with nicotine dependence increased from 31% to 70% and the number of dependent smokers with depression, ADHD, bipolar disorder, and personality disorder increased significantly more than among non-smokers. In Canada, Yang and D'Arcy (156) similarly found that depression among older adults smokers increased substantially more than among non-smokers over the years 1994-2014. For cannabis, several studies have found increases in overall use without corresponding increases in cannabis use disorder (157-165), although there is also some conflicting evidence (166)(167)(168).…”
Section: Aim : Understand the Association Between Unhealthy Behaviors...mentioning
confidence: 97%